Self-Aligning Capability of IPT Pads for High-Power Wireless EV Charging Stations - Namadmalan, Alireza; Tavakoli, Reza; Goetz, Stefan M.; Pantic, Zeljko (IEEE transactions on industry applications, 2022)
This article studies magnetic forces between transmitter (Tx) and receiver (Rx) coils in an inductive power transfer (IPT) system aiming to use those forces to align the coils and, consequently, improve power transfer. Due to its popularity, the analysis is conducted on a series-series compensated IPT system with planar spiral coils. The proposed method utilizes the bifurcation operation mode of the system and unloaded resonating receiver to maximize attractive force between magnetic couplers. Three-dimensional finite-element method simulations indicate that high-power IPT systems can develop enough attractive force to align coils even under nominal current. Regardless of the coil shape, e.g., spiral or Double-D (DD), the attractive forces tend to align the coils. Hence, a smart charging station can be devised based on self-aligning capability. Furthermore, this article proposes a mechanical structure to facilitate the attractive lateral force for the alignment of high power applications, i.e., wireless fast-charging stations. The forces are analyzed, modeled, and simulated for a 100-kW IPT system with an operating frequency of 20 kHz, while the self-aligning capability is experimentally verified on a downscale 11-kW prototype.